Reduced dose, but not reduced risk: rates of inappropriate apixaban dose reduction and stroke and bleeding incidence. (3rd October 2022) - Harrington, J; Arps, K; Wu, A; Carnicelli, A P; Chiswell, K; Chrischilles, E; Shantha, G; Vanwormer, J; Mundl, H; Viethan, T; Alexander, J H; Lopes, R D; et al.
Abstract: Introduction: Patients with atrial fibrillation (AF) should be prescribed standard-dose (5mg twice daily) apixaban for stroke prevention unless they meet 2 or more criteria: age ≥80, weight ≤60kg, and/or creatinine ≤1.5mg/dL, in which case a reduced-dose (2.5mg twice daily) is indicated. Despite this, some clinicians may also prescribe reduced-dose apixaban to patients who do not meet criteria for dose reduction, in an effort to reduce bleeding risk. Purpose: To assess apixaban prescribing patterns in patients with AF based on dose reduction criteria and to characterize baseline demographics and incidence of ischemic stroke, major bleeding, and intracranial hemorrhage (ICH) for patients stratified by standard-dose, appropriately reduced-dose, and inappropriately reduced-dose apixaban. Methods: Using pooled data from 8 large hospitals in PCORnet, a multicenter national healthcare research network, we assessed the standard and reduced-dose apixaban prescribing patterns for patients with AF, with additional stratification of patients prescribed 2.5mg based on presence or absence of 2+ criteria for dose reduction. We then assessed baseline characteristics and 5-year event rate of ischemic stroke, major bleeding, ICH and death. Results: Of 45, 947 patients with AF on apixaban and available dosing information, 38, 861 (85%) were prescribed apixaban 5mg and 7086 (15%) were prescribed 2.5mg. Of patients prescribed apixaban 2.5mg, 4321 (61%) did not meet criteria for dose reduction. Patients on reduced dose apixaban were more likely to be female and have comorbidities such as heart failure, hypertension, and prior ischemic stroke. These trends were more pronounced for patients meeting dose adjustment criteria than those not meeting criteria (Table 1). Unadjusted analyses found patients on 2.5mg of apixaban were significantly more likely to experience ischemic stroke, major bleeding, and all-cause death. Patients with 2+ dose reduction criteria on 2.5mg of apixaban had the highest rates of each event, but patients who were prescribed reduced dose without meeting criteria were also at elevated risk (Table 2). Conclusion: Many patients prescribed reduced-dose apixaban do not meet criteria for dose reduction. Because patients prescribed reduced dose apixaban are older and have more cardiovascular risk factors, their incidence of stroke, major bleeding, and death exceeds that of full dose treated patients. These risks exist both for patients who do and do not meet criteria for dose reduction, suggesting potential under-treatment for the majority of dose-reduced patients. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bayer